2014
DOI: 10.1088/0957-4484/25/41/415502
|View full text |Cite
|
Sign up to set email alerts
|

GaN nanowire coated with atomic layer deposition of tungsten: a probe for near-field scanning microwave microscopy

Abstract: GaN nanowires were coated with tungsten by means of atomic layer deposition. These structures were then adapted as probe tips for near-field scanning microwave microscopy. These probes displayed a capacitive resolution of ~0.03 fF, which surpasses that of a commercial Pt tip. Upon imaging of MoS₂ sheets with both the Pt and GaN nanowire tips, we found that the nanowire tips were comparatively immune to surface contamination and far more durable than their Pt counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Moreover, the electrical properties of GaN tips can be easily modified by varying the doping, which avoids the need for metal coatings. Recently, Weber et al reported using Ti/Al and tungsten coated GaN NW probes for near-field scanning microwave microscopy in AFM [19,20]. However, no data was shown to illustrate image resolution capabilities for scanning high-aspect-ratio structures or to compare the durability of these tips with conventional probes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the electrical properties of GaN tips can be easily modified by varying the doping, which avoids the need for metal coatings. Recently, Weber et al reported using Ti/Al and tungsten coated GaN NW probes for near-field scanning microwave microscopy in AFM [19,20]. However, no data was shown to illustrate image resolution capabilities for scanning high-aspect-ratio structures or to compare the durability of these tips with conventional probes.…”
Section: Introductionmentioning
confidence: 99%